Design and Implementation of A Smart Water Tank Monitoring System for Optimising Water Management on Campus - Boedy Irhadtanto; Muhammad Rinov Cuhanazriansyah; Adam Hendrawan (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2026)
The growth of the Internet of Things (IoT) is driving the development of monitoring systems capable of improving the efficiency of resource management, including in water management systems. This research aims to develop an IoT-based Smart Water Tank Monitoring system to support the real-time monitoring of water levels on campus. The research employed a Research and Development (R&D) methodology using the ADDIE model, comprising the stages of Analyse, Design, Develop, Implement, and Evaluate. The system developed integrates an HC-SR04 ultrasonic sensor, an ESP32 microcontroller, a local web-based dashboard, LED indicators, and historical data storage. Data collection techniques were carried out through observation, interviews, documentation, and system testing. The data were analysed using quantitative descriptive analysis, Mean Absolute Error (MAE) and Black Box Testing. The results of the study indicate that the system is capable of automatically monitoring water conditions, displaying information in real time, improving the effectiveness of monitoring, and supporting the efficient management of water resources.